"The place I long to be": Resilience processes in migrants - Roberto,Sandra (2016)
Migration has been addressed in studies with a marked focus on its obstacles and difficulties, particularly in the contact with the host country. Recognizing that migrating is a complex process that involves several hardships, it is imperative to understand how migrants overcome adversity and to become aware of the resources mobilised to be cultural adjusted. Based on the theoretical perspective of resilience, this study aims to understand the contexts of adversity, resources and adjustment of Cape Verde migrants in Portugal, who have migrated to continue their studies in higher education. The collected 10 biographical narratives revealed the meanings of their life journeys, both in their country of origin and in the host country. The analysis of the narratives allowed the understanding of the diversity of resilience processes among the participants. The adversities were related to two main dimensions: cultural differences and interpersonal relationships with the Portuguese. In terms of resources, participants stressed the importance of the Cape Verdean diaspora upon arrival to the new country. Along the length of stay for some migrants, this remained the main resource; however, others were developing belongings and significant attachments in a broader context. In terms of cultural adjustment, many configurations have emerged, standing for the fluid nature of the resilience process, which can occur in different ways.